2004
DOI: 10.1158/0008-5472.can-03-3801
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles Provide Insights into Early Malignant Potential and Skeletal Abnormalities in Multiple Endocrine Neoplasia Type 2B Syndrome Tumors

Abstract: Identifying the molecular basis for genotype-phenotype correlations in human diseases has direct implications for understanding the disease process and hence for the identification of potential therapeutic targets. To this end, we performed microarray expression analysis on benign (pheochromocytomas) and malignant (medullary thyroid carcinomas, MTCs) tumors from patients with multiple endocrine neoplasia (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 37 publications
6
63
0
Order By: Relevance
“…In addition, expression analysis of tumors from MEN2A and MEN2B patients was performed (Jain et al 2004). Although, we identified a much larger spectrum of differentially expressed genes, data from the present approach are generally consistent with these studies, indicating that genes involved in the process of cell growth and epithelial to mesenchymal transition are characteristic for MEN2A and MEN2B tumors respectively.…”
Section: Dysregulation Of Host Antitumor Response Mechanisms During Rsupporting
confidence: 80%
“…In addition, expression analysis of tumors from MEN2A and MEN2B patients was performed (Jain et al 2004). Although, we identified a much larger spectrum of differentially expressed genes, data from the present approach are generally consistent with these studies, indicating that genes involved in the process of cell growth and epithelial to mesenchymal transition are characteristic for MEN2A and MEN2B tumors respectively.…”
Section: Dysregulation Of Host Antitumor Response Mechanisms During Rsupporting
confidence: 80%
“…Additionally, CEA and other CEACAMs were previously reported to be the MTC-related gene. CEACAM6 and CEACAM7 are upregulated in patients with MEN2B-MTC, which has similar gene expression profiles to the human MTC cell line TT, bearing the RET 634 mutation (1,3,4,10). In support of this, our screening data indicated that TT cells expressed several CEACAMs, including CEACAM6, CEACAM7, and an MTCspecific CEACAM member CEACAM4 (Table 2).…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr)supporting
confidence: 71%
“…Because transcriptome profiles of a pure, normal population of C-cells are not available, we focused our attention on a previously analyzed set of profiles from metastatic medullary carcinomas (MTC) in MEN2B patients (Jain et al, 2004;Ippolito et al, 2005), as these tumors derive from C-cells. As a comparison, we used a set of profiles obtained from primary papillary thyroid carcinoma of follicular subtype (PTCF; International Genomics Consortium, expO).…”
Section: Isl1 Is Expressed In Medullary Thyroid Cancermentioning
confidence: 99%
“…The first data set (Jain et al, 2004;Ippolito et al, 2005) included samples from 11 medullary thyroid carcinomas (MTC, primary and metastatic) from MEN2B patients, which have been hybridized on Affymetrix GeneChip HG-U95Av2 arrays. The second data set (International Genomics Consortium, expO) included samples from 9 papillary thyroid carcinomas (follicular variant; PTCF), which have been hybridized on Affymetrix GeneChip Human Genome U133 Plus 2.0 arrays.…”
Section: Microarray Data Analysismentioning
confidence: 99%